Patient-Reported Outcomes From LIBRETTO-431: First-Line Selpercatinib Versus Chemotherapy With Pembrolizumab in RET Fusion-Positive NSCLC - Caicun Zhou, MD, PhD; Silvia Novello, MD, PhD; Pilar Garrido, MD, PhD; Christophe Dooms, MD, PhD; Jorge Alatorre-Alexander, MD; Niels Reinmuth, MD; Gill Worthy, PhD; Kim Cocks, PhD; Justin Williams, PhD; Hongmei Han, MS, MApSt; Minji K. Uh, PhD; Nalin Payakachat, PhD; et al. (JTO Clinical and Research Reports, 2025)
Introduction: The benefit of first-line selpercatinib versus platinum-based chemotherapy with or without pembrolizumab in patients with advanced RET fusion-positive NSCLC has been previously reported. The patient-reported outcomes (PROs) from the LIBRETTO-431 trial presented here further support the benefit of first-line selpercatinib in this patient population. Methods: In the intention-to-treat pembrolizumab population, 129 patients received selpercatinib and 83 patients received platinum chemotherapy with pembrolizumab (control). Time to confirmed deterioration (TTCD) of the NSCLC Symptom Assessment Questionnaire (NSCLC-SAQ) total score was a secondary end point. Additional PROs included changes in the NSCLC-SAQ total and individual symptom scores, European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire health-related quality of life, functioning and symptoms, patient-reported tolerability by the Functional Assessment of Cancer Therapy GP5 item (GP5), and symptomatic adverse events by PROs version of the Common Terminology Criteria for Adverse Events up to 1 year were reported. TTCD was defined as the time from randomization to first deterioration in score that met prespecified thresholds, confirmed at next assessment. Patient-reported tolerability was reported as the proportion of patients with side effect bother over time. Results: Selpercatinib delayed TTCD of all individual NSCLC-SAQ symptoms versus control. A clinically meaningful improvement in the NSCLC-SAQ total score (mean difference = −2.00, 95% confidence interval [CI]: −2.94 to −1.05) was also observed at 1 year for selpercatinib versus control. Selpercatinib delayed TTCD of physical (hazard ratio = 0.54, 95% CI: 0.38–0.76) and role (hazard ratio = 0.59, 95% CI: 0.37–0.93) functioning measured by European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire, with significantly improved physical functioning at 1 year versus control (mean difference = 8.09, 95% CI: 2.82–13.37; p = 0.003). The selpercatinib group reported better tolerability, as measured by GP5, with a lower proportion bothered by side effects compared with control (22.6% versus 39.7%, OR = 0.58, 95% CI: 0.33–0.99). Conclusions: These PROs, combined with the established efficacy and safety profile of selpercatinib, further support the use of first-line selpercatinib as a standard of care and highlight the importance of early and comprehensive genomic testing in patients with RET fusion-positive NSCLC.